Mengukur Tingkat Kepuasan Sistem Informasi Pemantauan Praktik Laut Terintegrasi dalam Pendidikan dan Pelatihan Maritim: Analisis PIECES - Arika Palapa (Akademika, 2024)
Maritime education and training are aimed at producing and enhancing seafarers' competencies. Monitoring training activities is an essential aspect, yet its execution still relies on non-integrated email systems. When monitoring is not integrated and solely relies on email, the monitoring process becomes less effective. This research aims to develop and test an application called OTMON (Online Monitoring) for overseeing maritime education and training (MET). The research method utilizes a research and development (R&D) approach with the ADDIE phases: Analyze, Design, Develop, Implement, and Evaluate. System needs analysis employs the PIECES approach to fulfill monitoring requirements in MET activities. A total of 67 respondents participated in this research. The findings indicate that users perceive a high level of satisfaction when using the OTMON application. The application can be optimally utilized as it employs the PIECES approach. The research implication is that online monitoring applications can be considered as an alternative for monitoring maritime education and training.